Pengaruh Relaksasi Autogenik Terhadap Tingkat Nyeri Pasien Pascaoperasi Urolithiasis Dengan Spinal Anestesi - El Halawah, Futuh; Wibowo, Tophan Heri; Sebayang, Septian Mixrova (Yayasan Jompa Research and Development, 2025)
Postoperative pain is a common problem in urolithiasis patients undergoing spinal anesthesia and may hinder recovery. Autogenic relaxation is a non-pharmacological method that can help reduce pain. This study aimed to examine the effect of autogenic relaxation on postoperative pain levels in urolithiasis patients with spinal anesthesia. A quasi-experimental design with a pretest–posttest control group was applied. A total of 50 respondents were selected using accidental sampling and divided into an intervention group receiving autogenic relaxation and a control group receiving only education. Pain levels were measured using the Numeric Rating Scale (NRS). Results showed a significant reduction in pain in the intervention group (p=0.001), while no significant change was observed in the control group (p=1.000). Between-group analysis after the intervention revealed a significant difference (p=0.001). In conclusion, autogenic relaxation is effective in reducing postoperative pain among urolithiasis patients with spinal anesthesia and may serve as a complementary therapy in postoperative pain management.